Hubungan kakitangan-pelatih dan tingkah laku agresif dalam kalangan pelatih muda di institusi pemulihan juvana - Nazirah Hassan; Fauziah Ibrahim; Nor Shaffika Izzaty Zaiedy Nor; Daniella Mokhtar (Penerbit Universiti Kebangsaan Malaysia, 2020)
Aggressive behavior and violence have become a culture among inmates in correctional facilities. The involvement in such behaviors can lead to long-lasting physical, mental and emotional harms among inmates, thus obstruct their rehabilitation process. This study primarily aims to investigate the level and pattern of aggressive behavior among young inmates in juvenile correctional facilities in Malaysia. It further examines the association between staff-inmate relationship and aggressive behavior. A survey study was conducted, involving 289 male and female young offenders, aged 12 to 21 years old, in eight juvenile correctional facilities in Malaysia. The survey used two instruments, including the Measuring the Quality of Prison Life (MQPL) and Direct and Indirect Behavioral Checklist-Scaled Version Revised (DIPC-SCALEDr). The findings demonstrate that 95 per cent of young inmates reported at least one activity indicative of aggressive behavior in a month. The DIPC-SCALEDr scored significantly higher on verbal and psychological forms of aggressive behavior. The findings also show that staff-inmate relationship dimension has significant influence on aggressive behavior. Poor relationships between staff and inmates is a form of correctional strain that can cause emotional distress, frustration and anger among inmates. Such conditions often lead to aggressive behavior. The study suggests to improve correctional facilities by enhancing positive interpersonal relationships between staff and inmates. The study has implications for policy improvement in juvenile correctional settings.